Examining the interplay between personality and teamwork on organizational commitment and employee performance - Usmar, Usmar; Sismiati, Sismiati; Sulaiman, Syarifuddin; Tamrin, Tamrin; Rudhan, Andi; Swy, Ignatio Katriel (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Employee performance has an important role in achieving goals and maintaining the good name of educational institutions. This research aims to analyze the direct influence of personality and teamwork on organizational commitment and employee performance. This research also analyzes the direct impact of organizational commitment on employee performance. To analyze the influence of personality and teamwork on employee performance through organizational commitment. The population in this study were all employees with civil servant and non-civil servant status. The sampling method was census sampling, so the total sample was 72 people. The data collection technique is by distributing questionnaires which are answered by respondents in accordance with the sample selection criteria. The analysis technique used is Partial Least Squares Structural Equation Modeling. The research results show that teamwork has a positive and significant effect on organizational commitment and employee performance. Future research could investigate more deeply the mechanisms by which teamwork influences employee performance.